2019
DOI: 10.3390/ma12203412
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bone Regeneration between Porcine-Derived and Bovine-Derived Xenografts in Rat Calvarial Defects: A Non-Inferiority Study

Abstract: The present study aimed to compare the bone-regeneration capacity of porcine-derived xenografts to bovine-derived xenografts in the rat calvarial defect model. The observation of surface morphology and in vitro cell studies were conducted prior to the animal study. Defects with a diameter of 8 mm were created in calvaria of 20 rats. The rats were randomly treated with porcine-derived (Bone-XP group) or bovine-derived xenografts (Bio-Oss group) and sacrificed at 4 and 8 weeks after surgery. The new bone regener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…The distribution of animals in their respective groups in the present study, as well as the number of specimens (n), was based on the principle of the 3 R's, in which there is a commitment by the world scientific community to follow the Russell-Burch Principles (1959) "reduction, replacement and refinement" in the use of animals that, increasingly, remain active in scientific and academic circles. Therefore, it was decided to not perform groups with defects filled only by clot, autogenous bone [3,17] or Bio-Oss ® [5,7,28,45], widely previously published in the literature, including the same methodology used in the present experiment and also from the same research group [39,[46][47][48], focusing on only in the originality and aims of the research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of animals in their respective groups in the present study, as well as the number of specimens (n), was based on the principle of the 3 R's, in which there is a commitment by the world scientific community to follow the Russell-Burch Principles (1959) "reduction, replacement and refinement" in the use of animals that, increasingly, remain active in scientific and academic circles. Therefore, it was decided to not perform groups with defects filled only by clot, autogenous bone [3,17] or Bio-Oss ® [5,7,28,45], widely previously published in the literature, including the same methodology used in the present experiment and also from the same research group [39,[46][47][48], focusing on only in the originality and aims of the research.…”
Section: Discussionmentioning
confidence: 99%
“…Biomaterials used as bone substitutes must be biocompatible, biodegradable and also form a scaffold for osteoconductivity, in addition to having porosity similar to the natural bone of the recipient bed and allowing the growth of osteoinductivity factors. Among the products available commercially in dentistry and orthopedic medicine, Geistlich Bio-Oss ® is noteworthy due to the several published scientific works and wide use in the world [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…When applied to rat calvarial defects, porcine-and bovine-derived xenografts have had similar effects in terms of new bone volume and area [12]. In a canine model, however, significantly more new bone formation and better bone bridging have been observed for porcine than bovine bone [13].…”
Section: Introductionmentioning
confidence: 96%
“…Although several studies have reported that chemical cross-linking methods can trigger foreign body response due to chemical agent residues [ 33 , 37 ], EDC tends to lower cytotoxicity, because it does not remain as part of the linkage, and is converted to water-soluble urea derivatives that are relatively noncytotoxic [ 31 , 38 , 39 , 40 ]. In a previous study in which two different bone grafts were implanted into rat calvarial defects with EDC-cross-linked collagen membrane, animals showed excellent bone regeneration, no inflammatory reaction, and no membrane collapse [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have examined the bone-regenerative effects of EDC-cross-linked membranes, most were laboratory or small animal studies [ 33 , 37 , 41 ]. Therefore, the aim of the present study was to assess the physiochemical properties of EDC-cross-linked collagen membranes and to evaluate their effects on GBR in a canine implant defect model.…”
Section: Introductionmentioning
confidence: 99%